ರತ್ನಗಿರಿಚೊ ಸರ್ದಾರ್ - John M Permannur (Karnataka Konkani Sahitya Academy, 2014)
This book is a collection of Three Konkani Plays
Ratnagiricho Sordar
Keywords: Konkani; ರತ್ನಗಿರಿಚೊ ಸರ್ದಾರ್; Ratnagiricho Sordar; Literature; Konkani; Konkani